Insight into the acid tolerance mechanism of Acetilactobacillus jinshanensis subsp. aerogenes Z-1 - Li, Qin; Hu, Kaidi; Mou, Juan; Li, Jianlong; Liu, Aiping; Ao, Xiaolin; Yang, Yong; He, Li; Chen, Shujuan; Zou, Likou; Guo, Mingye; Liu, Shuliang (Frontiers in Microbiology, 2023)
Several lactic acid bacteria (LAB) are double-edged swords in the production of Sichuan bran vinegar; on the one hand, they are important for the flavour of the vinegar, but on the other hand, they result in vinegar deterioration because of their gas-producing features and their acid resistance. These characteristics intensify the difficulty in managing the safe production of vinegar using strains such as Acetilactobacillus jinshanensis subsp. aerogenes Z-1. Therefore, it is necessary to characterize the mechanisms underlying their acid tolerance. The results of this study showed a survival rate of 77.2% for Z-1 when exposed to pH 3.0 stress for 1 h. This strain could survive for approximately 15 days in a vinegar solution with 4% or 6% total acid content, and its growth was effectively enhanced by the addition of 10 mM of arginine (Arg). Under acidic stress, the relative content of the unsaturated fatty acid C18:1 (n-11) increased, and eight amino acids accumulated in the cells. Meanwhile, based on a transcriptome analysis, the genes glnA, carA/B, arcA, murE/F/G, fabD/H/G, DnaK, uvrA, opuA/C, fliy, ecfA2, dnaA and LuxS, mainly enriched in amino acid transport and metabolism, protein folding, DNA repair, and cell wall/membrane metabolism processes, were hypothesized to be acid resistance-related genes in Z-1. This work paves the way for further clarifying the acid tolerance mechanism of Z-1 and shares applicable perspectives for vinegar brewing.